Juridical Review of the Role of the Witness and Victim Protection Agency (LPSK) in Protecting Child Victims of Sexual Violence in the Family Environment - Nurjannah Nasution (IHSA Institute, 2018)
Based on Article 1 point 5 of the Witness and Victim Protection Act, the Witness and Victim Protection Agency (LPSK) is an authorized institution to provide protection and other rights to witnesses and / or victims as referred to in this law. The problems in this research are how, first, the regulation of protection against violence that occurs in child victims of sexual violence in the family environment and how the role of Witness and Victim Protection Institutions in providing protection for child victims of sexual violence and how the rights of witnesses and victims of violations happen. The purpose of this study was to determine the legal provisions against sexual violence against children in the family environment and to determine the role of witness and victim protection agencies and the obstacles faced in disclosing cases of sexual violence against children in the family environment. The research method used in writing this thesis is normative legal research by studying and analyzing primary data in the form of laws and regulations, secondary data in the form of law books and related legal journals, related theses, and tertiary data in the form of websites. website from the internet. Protection and supervision of child victims of sexual violence after amendments to the law on protection of witnesses and victims, Article 5 regulates the rights of witnesses and victims.